2017
DOI: 10.18825/iremjournal.328968
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Usefulness of Net Income Versus Comprehensive Income in Terms of Firm Performance: Borsa Istanbul Case

Abstract: Based on the ongoing claims that comprehensive income measures financial performance better than net income, thus enhance the transparency and usefulness of financial statements, International Accounting Standard No.1 (IAS 1) allows reporting comprehensive income in a primary and separate financial statement. From this point forth, we compare the usefulness of comprehensive income with net income in terms of financial performance proxied by stock price, stock returns and operating cash flows. Using a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Analysis of the previous three models did not provide conclusive evidence concerning the superiority of comprehensive income over net income in predicting future operating cash flows, net income and comprehensive income for one period ahead. This result contrasts Dhaliwal et al (1999), Kanagaretnam (2009), Victoria (2015) and Acar and Karacaer (2017) who found evidence for the superior predictive ability of net income to comprehensive income. In addition, this result also contradicts Wakabayashi (2002), Goncharov and Hodgson (2008) and Khan (2012) who provided evidence for the superiority of comprehensive income over net income in predicting future cash flows.…”
Section: Results Of Testing Research Hypothesis Hmentioning
confidence: 56%
See 3 more Smart Citations
“…Analysis of the previous three models did not provide conclusive evidence concerning the superiority of comprehensive income over net income in predicting future operating cash flows, net income and comprehensive income for one period ahead. This result contrasts Dhaliwal et al (1999), Kanagaretnam (2009), Victoria (2015) and Acar and Karacaer (2017) who found evidence for the superior predictive ability of net income to comprehensive income. In addition, this result also contradicts Wakabayashi (2002), Goncharov and Hodgson (2008) and Khan (2012) who provided evidence for the superiority of comprehensive income over net income in predicting future cash flows.…”
Section: Results Of Testing Research Hypothesis Hmentioning
confidence: 56%
“…Such a result indicates the absence of a significant difference in the predictive power of net income and comprehensive income with regard to future cash flows resulting in rejecting hypothesis H 1 providing an evidence that the predictive ability of net income for future cash flows does not differ from that of comprehensive income for companies listed in the Egyptian stock exchange. This result contrasts Dhaliwal et al (1999), Kanagaretnam (2009), Victoria (2015) and Acar and Karacaer (2017) who found evidence for the superior ability of net income to compre-hensive income in predicting future cash flows justifying their results by the less transitory nature of net income compared to comprehensive income. In addition, this result also contradicts Wakabayashi (2002), Goncharov and Hodgson (2008) and Khan (2012) who provided evidence for the superiority of comprehensive income over net income in predicting future cash flows.…”
Section: Results Of Testing Research Hypothesis Hmentioning
confidence: 64%
See 2 more Smart Citations
“…The study revealed a favorable effect (Eva, María-Del-Mar, & Samuel, 2018). According to Merve and Semra (2017), investors perceive the financial information contained in comprehensive income to be more volatile, risky, transitory, and incomplete compared to net income, which leads to a decline in stock price.…”
Section: Comprehensive Income Reporting and Incomplete Revelation Hyp...mentioning
confidence: 97%